Antitubercular Evaluation of Some Novel 2-Imino-3-(4’-carboxamidopyridyl)- 5-arylidene-4-Thiazolidinones and Their Brominated Derivatives - K. Kashaw, Sushil; Kashaw, Varsha; Mishra, Pradeep; Kumar, Ajay (Asian Journal of Chemistry, 2011)
Antitubercular activities of some new 2-imino-3-(4'-carboxamido pyridyl)-5-arylidene-4- thiazolidinones and their brominated products, structurally related to isoniazid were evaluated. Structure of the synthesized compounds was confirmed by means of elemental analysis, IR spectra and 1H NMR spectral data and were consistent with the chemical structure. Antitubercular activities of compounds were done by liquid dilution method where MIC (minimum inhibitory concentration) were determined. Isoniazid was used as the standard drug for reference. Minimum inhibitory concentration of the compounds ranged between 11-23 μg/mL and some of the synthesized compounds showed significant inhibitory activities. It was concluded that arylidene nuclei at position 5 of the 4-thiazolidinone nucleus improved the antitubercular activity.